PERLINDUNGAN HUKUM TERHADAP PENOLAKAN KLAIM ASURANSI OLEH PERUSAHAAN ASURANSI - Chindy; Anissa Sylviana (Realism: Law Review, 2023)
The development of insurance in Indonesia has grown very rapidly, various types of insurance companies are offered to the public to participate in an agreement. In this study using normative juridical research methods using statutory approach (statue approach) and analytical approach (analytical approach). The focus of this research is how legal protection is against life insurance claims that are rejected by insurance companies and how cases of insurance claims are resolved by underage heirs. The purpose of this study is to determine legal protection for insurance claims that are rejected by insurance companies and settlement of insurance claim cases by heirs who are still underage. The results of this study produce a legal protection for heirs in submitting insurance claims that are rejected by insurance companies in the form of preventive and repressive legal protection. who are underage to claim insurance with the help of a power of attorney from a guardian or parent.